Study on Public Awareness and Perception on the Spreading of COVID-19 in Johor, Malaysia - Siva Kumar, Vilosha; Mohd Asrah, Norhaidah (Enhanced Knowledge in Sciences and Technology, 2021)
Coronavirus 2020 which is also known as COVID-19 infection spreading all around the world. The number of death cases keeps rising day by day. In Malaysia, the number of new cases keeps increasing. This has caused a significant effect on the population in Malaysia and Johor is one of the states that badly affected. This study is about the public awareness and perception of the spreading of COVID-19 in Johor. A survey is conducted and online survey forms have been forwarded through Whatsapp, Facebook, and Instagram. The methods applied in this study are Descriptive analysis, Pareto Analysis, and Chi-squared test. Cramer's V analysis is used to determine the level of association between the variables. Overall, the public in Johor is really aware of COVID-19 and satisfied with the measures taken by the Government